Assassinos seriais: uma abordagem psicanalítica sobre o superego arcaico e os efeitos da sideração - Monteiro, Klaylian Marcela Santos Lima (2012)
The present study aimed, in general, to investigate, under a psychoanalytic approach, the main processes that characterize the constitution of subjectivity of serial killers, linking them to the role that they play the ancient super-ego and the effects of stunning. As the first specific objective, there were submitted, from data collected in interviews, the aspects of the schizo-paranoid position and their repercussions in the manner that act serial killers, in this way, investigating the role of destructive fantasies, of defenses, besides the questions about the object-victims, passing by the theme of hate. The second specific objective was to study, from data collected in interviews, the ancient super-ego and its modes of action in those points related to sadism, to the criminal tendency, and the implications of the ancient super-ego on the psyche of the serial killers, besides the compulsion to repetition in the compulsive act of serial killers. The last of the objectives was the development of an interrelation between the data collected in the interview and the role of stunning in the psyche on the ancient superego demands. Search relevancy is justified, among other reasons, by the fact that it does not exist yet, in Brazil, psychoanalytic readings on this theme, in despite of the growing number of serial homicides and the need for improvement of clinical methods of early approach to children and adolescents who exhibit cases antisocial features. Such studies were marked out especially by kleinian and post-kleinian theoretical structure. It was noted that the psychic configuration of the serial killers, based on the model of ancient super-ego, takes them to destructive behaviors displayed in front of the victims, in particular, the ability to stunning. The data were obtained through interviews with serial killers prisoners in penitentiary units of the States of Rio de Janeiro and São Paulo